Classroom Social Environment as Student Emotions' Antecedent: Mediating Role of Achievement Goals. Issue 1 (2nd January 2022) - Sun, Xiaojing; Hendrickx, Marloes M. H. G.; Goetz, Thomas; Wubbels, Theo; Mainhard, Tim
Abstract: In line with assumptions made by the control-value theory of academic emotions, it was hypothesized that the association between the classroom social environment, in terms of students' perceptions of their teachers' interpersonal behaviour, and students' academic emotions was partially mediated by students' achievement goals. The present study applied multilevel structural equation modelling on questionnaire data from a sample of 2000 Chinese secondary school students. As assumed, achievement goals partially mediated the association between the classroom social environment and student emotions. Further, results indicated that the classroom social environment was more closely associated with student emotions than student goals were. The findings of this study add to the understanding of the antecedents of students' emotions in class.